Marāṭhī vaṅmayācā abhyāsa : Ṭhāṇẽ yethīla Marāṭhī granthasaṅgrahālayāce dahāve vārshika samārambhāce veḷi dilelẽ vyākhyāna - Āpaṭe, Hari Nārāyaṇa, 1864-1919 (SAMP early 20th-century Indian books project, 1921)
Study of Marathi literature, being a lecture delivered at the 10th annual celebration of the Marathi Library at Thana.